Pre Writing Strategies for Beginners EFL Studensts - Reny Nadeak (LPPM Universitas PGRI Adi Buana Surabaya, 2013)
To make students write, we teachers of writing have to get them involve with some activities. We keep them up and make them go through some stages of writing before they are assigned to do ‘real’ writing. The activities involve and occupy them both in groups or individually to experience some processes of learning like thinking, focusing on a specific topic , discussing and revising . Focusing on writing about things they like or interested in help them enliven communication and avoid writing block. This article introduce some pre writing strategies, alternatives the students can choose and motivate them to write better. They are ; 1).listing Ideas, 2).Free writing, 3). Brainstorming, 4).Preparing a scratch outline, 5). Guided writing and 6).Summarizing a reading selection.